BANKRUPTCY RISK AND FINANCIAL PERFORMANCE ANALYSIS (CASE STUDY OF INDOSAT OOREDOO PERIOD 2014 - 2018) - Ibnu Masud, Faisal
Around 2000 telecommunications operators gain high profit margin from voice and SMS (short messaging service). Currently, since VOIP (Voice Over IP) technology, followed by consumer shift to apps like WhatsApp, Facebook Messenger, Skype for communication purpose, then telecommunications revenue related to their core service become evaporating. On the other hand telecommunications operators must incur large CAPEX cost.